Gambaran Faktor Dominan Penyebab Rendahnya Akseptor IUD pada Pasangan Usia Subur - I Dewa Ayu Ketut Surinati (Jurnal Gema Keperawatan, 2014)
The purpose of this research was to know The Illustration Dominant Factors Cause Low IUD  acceptors . The methode of this research was discriptif with cross sectional design. The samples were consisted of 40 respondents selected with Consecutive sampling technique. These results indicate that, of the 40 respondents, 45% of respondents did not choose the contraceptive IUD as an option because of fear due to the lack of knowledge acceptors